2022
DOI: 10.3390/ijerph19052692
|View full text |Cite
|
Sign up to set email alerts
|

What Activities in Forests Are Beneficial for Human Health? A Systematic Review

Abstract: Over the past decade, clinical trials of forest-based interventions have increased, leading to their recognition as preventive medicine. However, little is known about the differences in health effects according to the activity characteristics of interventions. This study aimed to understand the types of activities and their associated health effects to identify differences in health effects between activities. PubMed, PsycINFO, Web of Science, and Scopus databases were searched, and methodological quality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 96 publications
(239 reference statements)
0
14
0
Order By: Relevance
“…Accumulated research provided positive evidence of nature-based therapy for the prevention and treatment of mental health problems, reduction of stress hormone levels, health regulating effects of green space, etc. ( Dzhambov et al, 2020 ; Park et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulated research provided positive evidence of nature-based therapy for the prevention and treatment of mental health problems, reduction of stress hormone levels, health regulating effects of green space, etc. ( Dzhambov et al, 2020 ; Park et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progressive growth of systemic reviews and meta-analyses suggested that the research showed a tendency from early empirical knowledge to potential non-pharmacological treatments, which will help nature therapy serve as preventive medicine to reduce medical expenditures of the whole society ( Yeon et al, 2021 ; Park et al, 2022 ). However, it is noteworthy that the systematic errors can affect the accuracy of the results of meta-analyses, such as different search strategies, selection criteria, research heterogeneity, and misestimated effect sizes caused by a small number of primary studies ( Mikolajewicz and Komarova, 2019 ; Rojas-Rueda et al, 2019 ; Rosa et al, 2021 ; Stier-Jarmer et al, 2021 ; Yeon et al, 2021 ; Park et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, more than half of the included studies did not provide a detailed randomization process and preregistered analysis plan. Thus, future investigations should utilize trial registry platforms and sophisticated randomization methods to improve the quality of evidence (15,208).…”
Section: Discussionmentioning
confidence: 99%
“…A recent surge in scientific and clinical trials on nature and health has led to the social acceptance of nature-based interventions (13)(14)(15)(16). Mounting evidence confirms the significant association between nature and health (1,(17)(18)(19); therefore, the World Health Organization and other health entities have emphasized nature as a health-promoting resource.…”
Section: Introductionmentioning
confidence: 99%